2020
DOI: 10.1590/2317-1782/20202019006
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of high resolution manometry in total laryngectomy

Abstract: Purpose: This study aims to measure the pressure of the pharynx and the pharyngoesophageal segment (PES) at rest and during phonation in total laryngectomized patients, with different levels of voice production. Methods: four total laryngectomized individuals participated in the study, All patients underwent High Resolution Manometry (MAR) at rest and during phonation. After this process, a descriptive analysis of the results was performed. Results: we observed that during rest the patients had PES pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…A small study with four patients used manometry at rest and during phonation, and found reduced pressure at the pharyngoesophageal segment from normal. This finding is thought to be related to changes within the pharyngoesophageal connections which also affect swallowing [28]. Patients with self-reported dysphagia also had higher hypopharyngeal intrabolus pressures, indicating restriction to bolus flow that reduced following dilatation, and were reliably correlated with a symptomatic improvement in swallowing [7].…”
Section: Manometric Assessment Of Swallowingmentioning
confidence: 98%
See 1 more Smart Citation
“…A small study with four patients used manometry at rest and during phonation, and found reduced pressure at the pharyngoesophageal segment from normal. This finding is thought to be related to changes within the pharyngoesophageal connections which also affect swallowing [28]. Patients with self-reported dysphagia also had higher hypopharyngeal intrabolus pressures, indicating restriction to bolus flow that reduced following dilatation, and were reliably correlated with a symptomatic improvement in swallowing [7].…”
Section: Manometric Assessment Of Swallowingmentioning
confidence: 98%
“…It is now recognized that most laryngectomy patients will have a degree of swallow dysfunction presenting as a propulsive and/or restrictive disorder [9]. In the instance of reduced pharyngeal propulsion, instinctive compensation is often seen with an effortful swallow correlating with manometrically recorded increased pressures at the top end of the swallow [26][27][28]. A propulsive swallow dysfunction can be further improved using therapeutic strategies including a smaller bolus, avoiding dry and particulate foods, and using a wash through swallow to clear any residue.…”
Section: Treatment Of Post Laryngectomy Dysphagiamentioning
confidence: 99%